PENGEMBANGAN BAHAN AJAR INTERAKTIF UNTUK PEROLEHAN KETERAMPILAN MENENTUKAN LUAS DAERAH YANG DIBATASI DUA FUNGSI - Suratman, Dede (Jurnal Pendidikan Matematika dan IPA, 2019)
Teaching materials are an important factor in the success of the learning process. This study aims to develop interactive electronic teaching materials for Calculus courses, especially the area of the region bounded above by function f,   below by function g, on the left by the line x = a, and the right by the line x = b, it is based on the needs of students and lecturers related to interactive materials. The method used is Research and Development methods with ADDIE procedures, that is, Analysis, Design, Development, Implementation, and Evaluation. In this paper, just until the implementation stage. The developed teaching materials consist of fully developed text, audio, and video media. Supporting software used are 3D Flipbook, Video Scribe, and Geogebra. Base on data analyss, the interactive electronic teaching materials can improve student skill to find the area of the region bounded by two functions.